A Moodle-Based Digital Learning Approach to Enhance AI Literacy Competence in Non-STEM Programs - Sigit Pambudi; Herman Dwi Surjono; Totok Sukardiyono; Akhsin Nurlayli (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2026)
This study aims to develop sontoto and evaluate a Moodle-based digital learning model to improve the artificial intelligence (AI) literacy of non-STEM students in a management program. To promote enactiveness, we designed ADDIE-based learning model with integrated case-based learning, project-based assignments, interactive H5P content and Gamification features. A one-group pretest–posttest olxtogel design was used on 50 undergraduate students. Data was collected through AI Literacy Tests, Learning Analytics and Questionnaires. Before hypothesis testing using the Shapiro–Wilk test, normality of data were assessed. Results of present t-test showed that students significantly reported improvement in their competence for AI literacy after education intervention (p <0.001) with a large effect size. Learning analytics uncovered high engagement, and a strong positive relationship with time spent on the learning modules that significantly correlated with posttest scores. The qualitative analysis also indicated that students of the learning environment perceived as relevant, motivating and encouraging the development of practical skills. While the absence of control group means these results have limitations as a basis for causative inference, they indicate that such an organically structured learning model based around Moodle could work feasibly in supporting AI literacy alexistoto development across non-STEM higher education cohorts. This study provides a guide about possible integration of pedagogical techniques and interactive technologies concerning AI literacy education.